Diagnosis by axilla skin biopsy in an early case of Lafora's disease. - Rubio, G (1992)
Myoclonus, seizures and progressive dementia are the main clinical features in Lafora's disease. This is the first reported case in which the diagnosis has been made by axillary skin biopsy in a patient with myoclonus but no other neurological symptoms.